LANDASAN HUKUM TERHADAP PERILAKU MAIN HAKIM SENDIRI DALAM PERSPEKTIF SOSIOLOGI HUKUM - Muhammad Riefky Alfathan; Riky Praasetia; Sailan Holilul Azfa; Rosyad Syahidin; Pratama Zulkarnaen; Beni Ahmad Saebani (CV Rewang Rencang, 2024)
This article examines the relationship between societal development and law in the context of social change influenced by globalization and technological progress. Using classical theories such as Auguste Comte's